Reading Habits of User Affecting Reading Culture in Public Library XYZ - Siti Nur Aidah JOHARI; Nurhidayah HASHIM; Mohd Yusof MUSTAFFAR (Communications of International Proceedings, 2020)
Based on the previous research, there are numerous studies done in order to identify the benefits of reading habits among user in the public library. The purpose of this research is to identify the ways to promote reading culture in Public Library XYZ. The significant of the research address how the reading habits of user affecting the reading culture in the Public Library XYZ. This study will give huge contribution to the library and society. As for the library, they can prepare a well plan activities and suitable materials to ensure the reading culture among users will sustain. The respondent of this study is among users from Public Library XYZ itself. The users will be determine based on their Library ID card or it call MyID that represent the membership or non-membership of the library users.
Keywords: Reading; Reading Habits; Reading Culture.